Enhancement of High‐Temperature Energy Storage in PEI Dielectrics Through Dual‐Function Scattering/Trap Layers - Meng, Zhaotong; Wang, Zhiqiang; Zhang, Tiandong; Zhang, Changhai; Li, Weixing; Zhang, Tongqin; Zhang, Jiaqi; Chi, Qingguo (Small (Weinheim an der Bergstrasse, Germany), 2025)
Dielectric capacitors are essential for the effective and dependable performance of new energy electronic circuits. However, energy storage dielectric materials still face significant challenges, including low energy density and poor thermal stability. In this study, polyetherimide (PEI), a high‐temperature‐resistant material, is selected as the subject of investigation. A bifunctional three‐layer structure is designed to effectively regulate charge carriers. The structure consists of a scattering electron layer (4‐NB/PEI) containing 4‐(dimethylamino)phenylboronic acid (4‐NB) and a trapping electron layer (F4TCNQ/PEI) containing 2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodimethane (F4TCNQ). The surface layer inhibits electron injection, while the intermediate layer suppresses high‐energy electron transport, leading to effective carrier regulation. The results demonstrate that the PEI composite achieves optimal performance when 2 µm of 4‐NB/PEI is used as the surface layer, with F4TCNQ/PEI serving as the intermediate layer. Under these conditions, the energy density reaches 6.14 J cm−3 at 150 °C, with an energy efficiency of 93.26%. Furthermore, the polarization electric field strength is 6.90% higher than that of the homogeneous 4‐NB doping. This improvement is due to the combined effects of the surface layer, which blocks electron injection, and the intermediate layer, which suppresses high‐energy electron transport. Additionally, the strong interfacial interactions between the layers effectively resist electron impact. This study develops a multilayer composite structure with electron‐repelling surface layers and electron‐attracting intermediate layers. The design enhances dielectric strength by leveraging scattering, capturing synergistic effects, and incorporating coulomb interlayer attraction forces, improving energy storage performance.